2012
DOI: 10.1111/j.1365-313x.2011.04871.x
|View full text |Cite
|
Sign up to set email alerts
|

Biotin deficiency causes spontaneous cell death and activation of defense signaling

Abstract: SUMMARYIn addition to its essential metabolic functions, biotin has been suggested to play a critical role in regulating gene expression. The first committed enzyme in biotin biosynthesis in Arabidopsis, 7-keto-8-aminopelargonic acid synthase, is encoded by At5g04620 (BIO4). We isolated a T-DNA insertion mutant of BIO4 (bio4-1) with a spontaneous cell death phenotype, which was rescued both by exogenous biotin and genetic complementation. The bio4-1 plants exhibited massive accumulation of hydrogen peroxide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 82 publications
(125 reference statements)
4
40
1
Order By: Relevance
“…Interestingly, this increase in defense gene expression is not accompanied by enhanced resistance to bacterial pathogens, possibly because this increased transcription is not correlated with an accumulation of the corresponding protein (Li et al 2012a).…”
Section: Abiotic and Biotic Stress Tolerancementioning
confidence: 94%
“…Interestingly, this increase in defense gene expression is not accompanied by enhanced resistance to bacterial pathogens, possibly because this increased transcription is not correlated with an accumulation of the corresponding protein (Li et al 2012a).…”
Section: Abiotic and Biotic Stress Tolerancementioning
confidence: 94%
“…Furthermore, based on enzyme activity and coexpression with BZO1, 1,4-DIHYDROXY-2-NAPHTHOATE-COENZYME A THIOESTERASE2 seems likely to oversee the conversion of BA-CoA to BA in peroxisomes . Finally, recent works have credited a suite of peroxisomal proteins with roles in immune responses (Taler et al, 2004;Lipka et al, 2005;Bednarek et al, 2009;Clay et al, 2009;Coca and San Segundo, 2010;Li et al, 2012;Rojas et al, 2012). Given that BA derivatives such as salicylic acid, benzoylglucosinolates, and phytoalexins are important for plant defense, it will be interesting to explore the roles of the peroxisomal BA biosynthetic proteins in defense-related functions.…”
Section: Ba Biosynthesis In the Peroxisomementioning
confidence: 99%
“…An example is the observed upregulation of biotin biosynthesis after infection with SG200Δ19A which is not observed in any of the tin mutant infections. In Arabidopsis thaliana it has been shown that biotin is critical for suppressing spontaneous cell death [22]. The fact that biotin biosynthesis appears upregulated may indicate a direct involvement of a specific effector for maintaining a certain level of this essential cofactor.…”
Section: Discussionmentioning
confidence: 99%